Estudo limnológico dos reservatórios Jaguari e Jacareí com ênfase na comunidade zooplanctônica - Gazonato Neto, Antonio José (Universidade Federal de São Carlos, 2013)
The zooplankton community plays an important role in the dynamics of aquatic ecosystems, especially in the energy flow and nutrient cycling. The density, the biomass, the taxonomic composition and the body size of these group are variables that can characterize in limnological terms a water body and can indicate the deterioration degree of the environment, as well the eutrophication levels of the system. The Jaguari and Jacareí reservoirs are located on the Cantareira system, one of the largest water producers systems in the world; nevertheless in recent decades the quality of the water has been altered due to human pressure, the reason why we sought to evaluate it according to the zooplankton structural variations. A sampling of this community, as well the gathering of physical and chemical water data, were performed on eight points, with taxonomic identification, the numerical count of the groups, the biomass and body size determination and the calculation of two biological indicator indices. The results obtained and analyzed in this study enable to characterize the Jaguari and Jacareí reservoirs as heterogeneous environments, the Jaguari predominantly eutrophic and the Jacareí oligotrophic. There was a relationship between the trophic states and the structure of the community for both samplings, as well as between Calanoida/Cyclopoida ratio and k-dominance curves with the levels of disturbance observed in the reservoirs by the constant supply of nutrients of Jaguari river. The biomass values and the body size structure of all species of the groups Cladocera and Copepoda were strongly associated with the trophy degree of both reservoirs. In reservoir Jaguari, the increasing of TSI was indicated by the increased nutrient concentrations and higher values of dominance and lower values of evenness and Shannon-Wiener index; for the Jacarei reservoir the lower trophic status and changes in the structure community, as evidenced by indicators indices and other variables, were less pronounced. Zooplankton community properties as indicators of reservoir trophic state are indeed adequate tools.
Keywords: Zooplâncton; Curvas ABC; Calanoida; Cyclopoida; Sistema da Cantareira (SP); Eutrofização; Razão Calanoida/Cyclopoida; Zooplankton; ABC curves; Calanoida/Cyclopoida ratio; Cantareira system; Eutrophication; CIENCIAS BIOLOGICAS::ECOLOGIA